Community Education on Sustainable Tofu and Tempeh Waste Management in Abian Tubuh Baru: Edukasi Masyarakat tentang Pengelolaan Limbah Tahu dan Tempe yang Berkelanjutan di Abian Tubuh Baru - Mega Nofitri Ikhwan; Azkiya Rahmani Sa’idah; Azra Alvina; Dekza Tri Sanusi; Humaira Azzahra (Yayasan Siti Widhatul Faeha, 2026)
The tofu and tempeh industry in Abian Tubuh Baru Village, Sandubaya District, Mataram City, contributes to local economic development but also has the potential to degrade river environmental quality due to inadequate waste management practices. This community service activity aimed to educate community members and tofu-tempeh business actors about the environmental impacts of industrial waste and to increase awareness of sustainable waste management using the DPSIR (Driving Force, Pressure, State, Impact, Response) framework. The activity was conducted from 23–26 May 2026 in Karang Pande, Abian Tubuh Baru Village, through field observations, environmental problem identification, development of DPSIR-based educational materials, and dissemination of leaflets and posters. Observations revealed direct wastewater disposal into drainage channels connected to the Unus River, accumulation of organic waste residues, unpleasant odors, and visible signs of declining environmental quality. Based on these findings, DPSIR-based educational materials were developed and distributed to facilitate public understanding of the causal relationship between industrial activities and environmental conditions. The activity demonstrated that the DPSIR framework can effectively communicate local environmental issues in a simple and contextual manner. Therefore, DPSIR-based environmental education has the potential to strengthen community awareness and support sustainable river ecosystem management through increased public participation in environmental conservation efforts.